2011
DOI: 10.4049/jimmunol.1002621
|View full text |Cite
|
Sign up to set email alerts
|

Immune Evasion ofMoraxella catarrhalisInvolves Ubiquitous Surface Protein A-Dependent C3d Binding

Abstract: The complement system plays an important role in eliminating invading pathogens. Activation of complement results in C3b deposition (opsonization), phagocytosis, anaphylatoxin (C3a, C5a) release, and consequently cell lysis. Moraxella catarrhalis is a human respiratory pathogen commonly found in children with otitis media and in adults with chronic obstructive pulmonary disease. The species has evolved multiple complement evasion strategies, which among others involves the ubiquitous surface protein (Usp) fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 85 publications
0
33
0
Order By: Relevance
“…3A, fulllength UspA2 30 -539 (amino acids 30 to 539 of UspA2) of M. catarrhalis Bc5 bound plasminogen in a dose-dependent manner, as determined by an ELISA. To pinpoint the plasminogen-binding region of UspA2, a series of truncated recombinant proteins were used (8,9,14). Our results revealed that all UspA2 fragments, except for UspA2 165-318 and UspA2 , significantly bound plasminogen in comparison with the negative-control protein YfeA.…”
Section: Uspa2 and Uspa2h Are The Major Plasminogen-binding Proteins mentioning
confidence: 84%
See 3 more Smart Citations
“…3A, fulllength UspA2 30 -539 (amino acids 30 to 539 of UspA2) of M. catarrhalis Bc5 bound plasminogen in a dose-dependent manner, as determined by an ELISA. To pinpoint the plasminogen-binding region of UspA2, a series of truncated recombinant proteins were used (8,9,14). Our results revealed that all UspA2 fragments, except for UspA2 165-318 and UspA2 , significantly bound plasminogen in comparison with the negative-control protein YfeA.…”
Section: Uspa2 and Uspa2h Are The Major Plasminogen-binding Proteins mentioning
confidence: 84%
“…catarrhalis clinical isolates exhibit a high degree of serum resistance (7)(8)(9). This serum resistance is dependent on the acquisition of host serum complement regulators such as vitronectin, factor H, and C4BP and the complement components C3 and C3d (9,(11)(12)(13)(14). Clinical isolates of M. catarrhalis have variable serum resistance that cannot be correlated with the recruitment of a single complement inhibitor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The central component of all complement activation pathways is C3b, and therefore, all pathogens causing invasive diseases would benefit from inhibiting deposition or function of C3b on their surface, either by attracting host FH or by inhibiting C3b directly (20,21). Increasing numbers of microbes have been shown to acquire FH onto their surfaces to protect themselves from complement attack (21).…”
mentioning
confidence: 99%